Сороміцький елемент в українському танцювально-приспівковому фольклорі (до проблеми творення інструментального кітчу) - Хай М. (Народна творчість та етнографія, 2007)
The questions associated with the obscene element in dancing-refrain folklore during the decades were prohibited to mention and study. But obscene elements always were distinctive features of the ethnic culture. The goal of this research is generalization of the experience collected in the memory of the performers through more than three decades, in order to analyse every day behavior and situations through the dancing-refrain traditions, associated with obscene folk elements. Author is studying the particularities of traditional Ukrainian obscene elements in dancing-singing traditions of Ukrainians in various regions and comparing his own materials with the recordings from the nineteenth century.